2010
DOI: 10.1249/mss.0b013e3181e39788
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise and Heat-Induced Hypohydration on Brain Volume

Abstract: Purpose: The aim of the present study was to quantify changes in brain volume following exercise/heat-induced hypohydration in man. Methods: Eight active men completed intermittent exercise in a warm environment, until 2.9 ± 0.1 % of body mass was lost. Subjects remained hypohydrated for two hours following the end of exercise. Brain volume was measured before, immediately following, and 1h and 2h after exercise using MRI (Philips 3T Achieva). Measures of subjective feelings and core body temperature were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…There is some limited evidence that dehydration results in a change in brain volume [43], but this response has not been demonstrated in all studies [44]. Dehydration [45] and hyperthermia [46] also appear to result in transient opening of the blood–brain barrier, and this may have implications for the stability of the cerebral environment during exercise.…”
Section: Use Of Nutrition To Influence Central Fatiguementioning
confidence: 99%
“…There is some limited evidence that dehydration results in a change in brain volume [43], but this response has not been demonstrated in all studies [44]. Dehydration [45] and hyperthermia [46] also appear to result in transient opening of the blood–brain barrier, and this may have implications for the stability of the cerebral environment during exercise.…”
Section: Use Of Nutrition To Influence Central Fatiguementioning
confidence: 99%
“…It is well documented that even moderate levels of dehydration increase physiological strain, most likely via disproportionately elevation in heart rate and a concomitant reduction in cardiac output, resulting in body’s inability to dissipate heat (12, 13). Furthermore, water losses ≥ 2% of total body weight impair significantly exercise and skill performance (1, 5) both in laboratories and field studies as well as mental performance in hot environments (7, 27, 28). Moreover, recent studies indicated that even lower levels of dehydration (~ −1%) provoke unfavorable changes in the athletic performance (6, 18).…”
Section: Introductionmentioning
confidence: 99%
“…They reported no significant effect of dehydration on brain volume. Results on ventricular volume ranged from decrease 12 to increase, 7,10 and Dickson et al found no changes. 11 Duning et al 13 showed a 0.55% brain volume reduction after 16 hours of thirsting and a 0.72% increase after subsequent rehydration.…”
mentioning
confidence: 96%
“…Previous brain morphometry findings in healthy subjects undergoing de- and rehydration have remained somewhat inconclusive and inconsistent in terms of the distribution of the changes and the structures affected. Kempton et al, 7,10 Dickson et al, 11 and Watson et al 12 induced dehydration by thermal exercises. They reported no significant effect of dehydration on brain volume.…”
mentioning
confidence: 99%